Do Socio-Cultural Factors Affect Speaking Anxiety? A Case Study of Non-English Major Students in West Java - Vanalestari, Adisty; Setyarini, Sri (Allure Journal, 2025)
Anxiety in foreign language speaking is a widely studied aspect in EFL contexts. Identifying the factors contributing to students' speaking anxiety is essential for understanding and addressing this issue. A few anxiety students have indicated certain sociocultural factors, among other factors, could be responsible for students' foreign language speaking anxiety. Therefore, this study aims to investigate the social-cultural factors causing English-speaking anxiety in non-English primary undergraduate students. This study used a case study qualitative approach. The data collection used are in-depth semi-structured interviews. The data was collected from four undergraduate non-English majors in West Java. The data was analyzed using an open coding method to examine participants' opinions on the socio-cultural elements that impact English speaking anxiety. The data revealed several social-cultural related sources of speaking anxiety, including social and cultural environment, communicative apprehension, formal classroom environment, social status and self-identity, gender, and dialect. Collectively, these factors increase students' anxiety during speaking activities. Moreover, these sociocultural factors not only undermine students' confidence and willingness to take part in speaking tasks, but also hinder their overall progress in language learning. The results of this research are expected to offer helpful recommendations to enable English teachers or lecturers to react to their students' speaking anxiety and to assist teachers of lecturers in arranging their classes in a way that may reduce their students' speaking anxiety and promote students' speaking skills.Â